2015
DOI: 10.3174/ajnr.a4515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for Blunt Cerebrovascular Injury: Review of the Literature and a Cost-Effectiveness Analysis

Abstract: BACKGROUND AND PURPOSE: Evaluation for blunt cerebrovascular injury has generated immense controversy with wide variations in recommendations regarding the need for evaluation and the optimal imaging technique. We review the literature and determine the most cost-effective strategy for evaluating blunt cerebrovascular injury in trauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 33 publications
(55 reference statements)
1
17
0
Order By: Relevance
“…There seem to be a clear correlation between improved CT technology and diagnostic accuracy: Modern CT scanners with 16-, 32- and 64 -channel technology demonstrate higher sensitivity and specificity with increasing number of slices per rotation [ 58 , 59 , 61 63 ]. In a cost-effectiveness study by Malhotra et al CTA was found to be superior to DSA in patients selected for imaging based on the Denver screening criteria [ 42 ]. Eastman and co-workers significantly reduced time from injury to diagnosis of BCVI from 31.2 h to 2.65 h when converting from DSA to CTA.…”
Section: Resultsmentioning
confidence: 99%
“…There seem to be a clear correlation between improved CT technology and diagnostic accuracy: Modern CT scanners with 16-, 32- and 64 -channel technology demonstrate higher sensitivity and specificity with increasing number of slices per rotation [ 58 , 59 , 61 63 ]. In a cost-effectiveness study by Malhotra et al CTA was found to be superior to DSA in patients selected for imaging based on the Denver screening criteria [ 42 ]. Eastman and co-workers significantly reduced time from injury to diagnosis of BCVI from 31.2 h to 2.65 h when converting from DSA to CTA.…”
Section: Resultsmentioning
confidence: 99%
“…The estimated incidence of BCVI among all blunt trauma patients, presenting in high-volume, well equipped trauma centers is around 1-2% [12,13]. Although aggressive screening has led to the identification of more BCVI cases, debates remain due to costs and potential complications caused by (invasive) screening methods such as angiography [14][15][16]. Therefore, a standard screening method with high accuracy and low complication rate is needed for an adequate evaluation of the true incidence of BCVI.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, firstly, DSA is an invasive method of examination with excellent sensitivity, but its risk implies it should not be used as a preferred item for patients [73]. Secondly, the cost of DSA inspections is still a factor that cannot be ignored [74]. Thirdly, the difficulty of DSA operation, including requirements for contrast dose and pressure for injection, is also a major challenge for clinicians [75].…”
Section: Multiple Imaging Technologies For Tiamentioning
confidence: 99%